IMPLEMENTASI MODEL PEMBELAJARAN KREATIF DAN PRODUKTIF DALAM UPAYA PENINGKATAN MUTU PENDIDIKAN GURU - Purnama, Diana Septi (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Education effort is especial in improvement of human resourcequality owning high creativity and high independence very strategiclooked into productive and creative learning model in the effortdeveloping Human Resource matching with growth of world of IPTEK,to gain professional in his area.Human resources which was quality started from the attending ofcertifiable grad. In realizing quality of grade from each every educationinstitution, can be strived to [pass/through] activity of learning. Teacherhave duty and role in choosing and developing strategy learning ofwhich can give experience learn developing student potency in anoptimal fashion in order to become human being of inovative, adaptiveand creative.Education process which is condusive where student can learn withpleasure and excite so that have autodidact motivation which is andal.Other assumption express that school have failed is not in presentingacademic profile but in strengthening relation link which is the full ofwarm feeling, constructive, can grow to feel each other loving and canbear selfregard sense of belonging, this was necessary for teacher toreach efficacy of learning.